2000
DOI: 10.1093/cercor/10.11.1093
|View full text |Cite
|
Sign up to set email alerts
|

Partially Overlapping Neural Networks for Real and Imagined Hand Movements

Abstract: Neuroimagery findings have shown similar cerebral networks associated with imagination and execution of a movement. On the other hand, neuropsychological studies of parietal-lesioned patients suggest that these networks may be at least partly distinct. In the present study, normal subjects were asked to either imagine or execute auditory-cued hand movements. Compared with rest, imagination and execution showed overlapping networks, including bilateral premotor and parietal areas, basal ganglia and cerebellum. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
503
4
16

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 829 publications
(599 citation statements)
references
References 59 publications
76
503
4
16
Order By: Relevance
“…A reason for this may be that motor imagery is more difficult for patients so that additional neural resources are recruited for task performance. However, most previous studies in healthy subjects showed that neither movement complexity (as an operationalization for movement difficulty and task demands) nor motor imagery proficiency affect the neuroanatomical correlates of MI (Boecker et al, 2002;Gerardin et al, 2000;Guillot et al, 2008;Lehericy et al, 2004) (but see Kuhtz-Buschbeck et al, 2003). Thus, an alternative explanation would be that the extended activations in patients as compared to HVs mimic the pattern observed for overt attempted execution.…”
Section: Motor Imagerymentioning
confidence: 93%
See 1 more Smart Citation
“…A reason for this may be that motor imagery is more difficult for patients so that additional neural resources are recruited for task performance. However, most previous studies in healthy subjects showed that neither movement complexity (as an operationalization for movement difficulty and task demands) nor motor imagery proficiency affect the neuroanatomical correlates of MI (Boecker et al, 2002;Gerardin et al, 2000;Guillot et al, 2008;Lehericy et al, 2004) (but see Kuhtz-Buschbeck et al, 2003). Thus, an alternative explanation would be that the extended activations in patients as compared to HVs mimic the pattern observed for overt attempted execution.…”
Section: Motor Imagerymentioning
confidence: 93%
“…These areas are involved in motor control in general (Gerardin et al, 2000;Roland, 1984;Stephan et al, 1995) and in posture control of the wrist in particular (Suminski et al, 2007). In patients, the attempt to overtly move the left (paretic) wrist recruited the same areas plus a number of additional regions.…”
Section: Motor Executionmentioning
confidence: 99%
“…These regions have been involved in a number of studies in motor imagery (see reviews from Grèzes and Decety, 2001;Munzert et al, 2009). Several studies using neuroimaging (Kosslyn et al, 2001), transcranial magnetic stimulation (Ganis et al, 2000), or clinical investigations (Sirigu et al, 1996) showed that motor imagery shares neural mechanisms with movement planning (Decety et al, 1989) and movement execution (Gerardin et al, 2000;Parsons et al, 1995), in particular in premotor cortex (e.g. Ionta et al, 2010) and parietal cortex (e.g.…”
Section: Shared Spectral and Anatomical Mechanisms Between Motor Imagmentioning
confidence: 99%
“…These studies show the existence of a cortical and subcortical network activated during both motor imagery and action observation. This network involves structures directly concerned with motor execution, such as motor cortex, dorsal and ventral premotor cortex, lateral cerebellum, basal ganglia; it also involves areas concerned with action planning, such as dorsolateral prefrontal cortex and posterior parietal cortex (see [49]). Concerning primary motor cortex itself, fMRI studies unambiguously demonstrate that pixels activated during contraction of a muscle are also activated during imagery of a movement involving the same muscle [50].…”
Section: The Simulation Theory: From Motor Imagery To Action Attributionmentioning
confidence: 99%